Into the Wild: Divergence-Convergence Dynamics in Frost’s ‘The Road Not Taken’ and O’Donohue’s ‘For the Traveller’ - Dhungel, Nabaraj (Pursuits: A Journal of English Studies, 2025)
This paper attempts to explore and analyze how Frost and O’Donohue show the dynamics of divergent journey and convergent journey of a traveler through their poems ‘The Road Not Taken’ and ‘For the Traveller’ respectively. This study displays the poets’ focus on significant contribution of the travel and experiences from it to create a difference in the lives of human beings. The speakers in both poems make a divergent journey to the unexplored and strange vast world outside which leads them to realization of inner transformation. It is the beauty of the startling journey outward to the wild which enlightens and enriches the humans leading to inner journey to the self and thereby balancing the external and the internal. Both Frost and O’Donohue endeavour to glorify the value of travel in human life as it broadens our mind, liberates our heart and pacifies our souls creating a total balance in life. It is the journey that brings the opposites together changing the scary into the merry. This research projects that the journey to the wild, startling, infinite, unexplored and untraveled seems to be problematic in the beginning but it turns out to be fruitful and significant ultimately as it leads to formation, transformation and reformation of the self. To justify the argument, the ideas of Carl Thompson and Susan Bassnett have been used. This writing plays a significant role in advancement of human life as it efforts to encourage people to make travel to the unknown by unraveling the mysterious strength of journey whether it is divergent or convergent.